MENGEMBANGKAN KARAKTER SISWA DALAM PEMBELAJARAN BAHASA DENGAN MODEL PERSONAL-KOOPERATIF - Siti Rochmiyati (Universitas Sarjanawiyata Tamansiswa, 2017)
â€œPendidikan Budaya dan Karakter Bangsaâ€ as a national movement was already planned by Kemdiknas since 2010 must be appreciated and implemented by every teacher. Student as subject learners has two kind of development dimension that is individual human and social human wich is accountable as God creation. Both of it with character educationâ€™s value is also important as a component for the development of learning innovation that must be familiarized and strengthened. Therefore, learning model that elaborating personal and social learning can be an alternative implementation of character education optimally. There are four language skills as basic learning in language learning. That matter involves speech, hearer, and speech media. Through this listening, speaking, reading, and writing skills, character education can be familiarized at once trained religiously.